The Influence of Perceived Value on the Purchase Intention of New Energy Vehicle Consumers: Empirical Evidence from Nanjing, China - Pathak, Shubham; Zhaung, Yunke (Science, Technology, and Social Sciences Procedia, 2024)
The new energy vehicles (NEVs) industry is one of the 7 strategic emerging industries in China and represents the key trajectory of the future automobile industry. The Chinese government strongly supports and promotes the innovative development of the new energy vehicle industry. The development and use of automobiles cannot be separated from the purchase and support of consumers, and consumers tend to buy brand products suitable for themselves. This study explores the impact of consumers’ perceived value on the purchase intention of new energy vehicles. The research follows the quantitative methodology. This paper analyzes consumers’ purchase intention from 4 aspects of perceived value. The hypothesis was verified by regression analysis and questionnaire data was collected. The research object is Nanjing citizen consumers. The results show that perceived price value, perceived quality value, perceived emotional value and perceived social value have significant positive effects on the purchase intention of Nanjing consumers. The results of this study will help to enhance the market competitiveness of new energy vehicle brands, provide certain references for stakeholders in the new energy vehicle industry, and promote the development of the new energy vehicle industry.